Effect of Heat Processing of Rubber Seed Kernel on In Vitro Rumen Biohydrogenation of Fatty Acids and Fermentation - Nirawan Gunun; Metha Wanapat; Chatchai Kaewpila; Waroon Khota; Sineenart Polyorach; Anusorn Cherdthong; Rattikan Suwannasing; Pairote Patarapreecha; Piyawit Kesorn; Piyawan Intarapanich; Nuttabodee Viriyawattana; Pongsatorn Gunun (My University, 2023)
The aim of this study was to assess the effect of rubber seed kernel heat processing on in vitro rumen biohydrogenation of fatty acids and fermentation. The experiment was conducted with a completely randomized design (CRD). The inclusion of RSK at 0% (CON) and 20% with different processing methods as follows: Raw rubber seed kernel (RAWR), roasted rubber seed kernel (ROR), microwave irradiated rubber seed kernel (MIR), and rubber seed kernel were heated in a hot air oven (RHO) in total mixed ration (TMR) diets. The hydrogen cyanide (HCN) was reduced using RSK heat methods. The heat processing of RSK had no effect on cumulative gas production at 96 h, the gas production from the insoluble fraction (b), or degradability (p > 0.05), whereas it reduced the gas production from the immediately soluble fraction (a) and constant rate of gas production for the insoluble fraction (c) (p < 0.01). The RSK processing methods did not influence ruminal pH, total volatile fatty acid (VFA), or VFA proportions (p > 0.05). RSK heat processing reduced ammonia-nitrogen (NH3-N) (p < 0.04) while increasing the bacterial population (p < 0.02). Heat treatment had no effect on linoleic acid (C18:2 cis-9,12 + tran-9,12) (p > 0.05). The RHO increases oleic acid (C18:1 cis-9 + tran-9) and linolenic acid (C18:3 cis-9,12,15) concentrations (p < 0.01). In conclusion, RHO reduced rumen biohydrogenation of unsaturated fatty acids (UFA), especially C18:3 and C18:1.
Keywords: Linolenic acid; Ruminant Nutrition and Digestive Physiology